2019
DOI: 10.1016/j.anr.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Person-Centered Perioperative Nursing Scale

Abstract: a b s t r a c tPurpose: The purpose of this study was to develop a scale to measure person-centered perioperative nursing (PCPON) and validate its psychometric properties. Methods: The preliminary items of the PCPON scale were developed through a literature review, indepth interviews, and content validity analysis. A total of 459 nurses working in the operating rooms of 21 hospitals in Korea responded to the questionnaire from September to October 2017. The collected data were analyzed by exploratory factor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Several different focuses and studies have reported the need to seek a consensus with respect to the term, the humanization of care, which would contribute systematically to its development in the field of health [2]. In this respect, previous studies have agreed that the humanization of care is built upon people’s needs in the care relationship [4,10,11,16], for which purpose healthcare professionals must be committed to their work [17,21,22,23], which is promoted if they possess certain characteristics [27,28,29,34,39,40,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several different focuses and studies have reported the need to seek a consensus with respect to the term, the humanization of care, which would contribute systematically to its development in the field of health [2]. In this respect, previous studies have agreed that the humanization of care is built upon people’s needs in the care relationship [4,10,11,16], for which purpose healthcare professionals must be committed to their work [17,21,22,23], which is promoted if they possess certain characteristics [27,28,29,34,39,40,46].…”
Section: Discussionmentioning
confidence: 99%
“…The approach to and use of the term “humanization” is very much present in the area of care, and has even come to be defined as the humanization of care, arising in response to the perception of a society where healthcare is dehumanized or depersonalized [1,2,3,4]. This is a situation that, even though considered multifactorial [5], may be associated to a great extent with emotional exhaustion, burnout [6,7,8], stress [2] or other factors more closely associated with the workplace, such as staffing ratios or the automation of care [2,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various effects of PFCC have been reported; however, autonomous decision-making and family visitation are relatively difficult in Korea owing to doctor-centred intensive treatment, limited time and related policy (Lee & Yi, 2017). Several studies on PFCC in ICUs have been conducted worldwide, including analysing the concept , developing measures (Kang et al, 2018;Shin & Kang, 2019;Van Haitsma et al, 2014) and examining the effects of person-centred nursing interventions (Eaton, Roberts, & Turner, 2015). However, there are scant studies concerning PFCC in Korea (e.g.…”
mentioning
confidence: 99%
“…However, there are scant studies concerning PFCC in Korea (e.g. Kang et al, 2018;Kang & Lim, 2019;Shin & Kang, 2019), and the existing research lacks an examination of ICU nurses' perspectives. Therefore, we examined nurses' experiences with and opinions concerning PFCC before and after applying a family-visiting programme, which was developed to reflect ICU characteristics, the Korean health care system and Korean family culture and relations.…”
mentioning
confidence: 99%